CATHOLIC SPIRIT OF ASSOCIATION: CATHOLIC POPULAR CULTURE, CONFRATERNITIES, GUILDS AND a RESTORED COMMUNITY IN THE INDUSTRIAL DIOCESE OF LATE VICTORIAN-EARLY EDWARDIAN WEST RIDING OF YORKSHIRE. (2nd July 2020) - Holmes, David
Abstract : If we wish to test the strength of the Catholic spirit in the industrial Diocese of late Victorian early Edwardian West Riding of Yorkshire, we should first consider what types of institutions and societies existed among them. Thus, wherever the spirit of Catholicism flourished in the hearts of the laity, it should manifest itself in the Church's different confraternities, guilds and societies. These Catholic institutions functioned mostly independent of each other but controlled by the central council of the Church. They were an effective means of developing a new Catholic identity with forms of self-legitimisation that would come to increase Irish Catholic communal and religious life. They were indispensable to the cultural expansion of the Church and the spirit of Catholic association. The immediate purpose of these societies was a moral and spiritual provision, but they achieved much more than this. These societies worked side by side with the Catholic Church and mutually supplemented each other, becoming the twin children of the same spirit. They owed their existence to the same powerful reaction of the Church against the moral and material deterioration of English Protestant society.